India and China on the War in Ukraine: A Comparative Analysis [version 2; peer review: 1 approved, 3 approved with reservations] - Malgorzata Bonikowska (Stosunki Międzynarodowe)
Background The Russian invasion of Ukraine has divided the world. While the Western countries have formed a coalition to support Ukraine, Global South states have adopted more nuanced positions. Within BRICS, both China and India have sought to leverage the conflict to advance their own strategic interests. Method This study analyses dominant narratives in Indian and Chinese media between 25 February 2022 and 30 June 2024. Using qualitative content analysis of 485 news and commentary items, it tests the hypothesis that regime type shapes narrative uniformity. Results China’s authoritarian system produces markedly more cohesive, state-aligned narratives, whereas India’s hybrid democracy exhibits greater heterogeneity. Nevertheless, both converge on calls for multipolarity, sanctions scepticism and diplomatic settlement. Conclusions Regime characteristics condition narrative diversity, yet strategic ambivalence enables both states to maximise autonomy in a fragmenting order.